2015
DOI: 10.1515/revneuro-2014-0044
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic role of neuronal nicotinic acetylcholine receptors in epileptic disorders: implication for pharmacological interventions

Abstract: AbstractAccumulating evidence suggests that neuronal nicotinic acetylcholine receptors (nAChRs) may play a key role in the pathophysiology of some neurological diseases such as epilepsy. Based on genetic studies in patients with epileptic disorders worldwide and animal models of seizure, it has been demonstrated that nAChR activity is altered in some specific types of epilepsy, including autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) and juvenile myoclonic epilepsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 180 publications
0
25
0
Order By: Relevance
“…Increased cholinergic tone may reflect an attempt to compensate for a progressively dysfunctional system, similar to what is observed in human prodromal AD where ChAT activity increases in the forebrain before ultimately decreasing as dementia progresses [8387,99]. However, the association between poorer performance suggests a maladaptive compensatory response, similar to that reported following temporal lobe epilepsy [100,101]. …”
Section: Discussionmentioning
confidence: 80%
“…Increased cholinergic tone may reflect an attempt to compensate for a progressively dysfunctional system, similar to what is observed in human prodromal AD where ChAT activity increases in the forebrain before ultimately decreasing as dementia progresses [8387,99]. However, the association between poorer performance suggests a maladaptive compensatory response, similar to that reported following temporal lobe epilepsy [100,101]. …”
Section: Discussionmentioning
confidence: 80%
“…Gene mutations identified in the CHRNA4, CHRNB2, and CHRNA2 genes in ADNFLE families strongly establish the role of the cholinergic system in this type of epilepsy, where functional characterization of known mutations suggests that increased gain of the receptor function is at the origin of seizures. 30 Furthermore, in vitro and in vivo studies have demonstrated a high density of nAChRs in the thalamus, 31,32 an overactivated cholinergic pathway, reinforcing the hypothesis that corticosubcortical networks, regulating arousal from sleep, play a central role in the epileptogenesis of NFLE. The major finding of the present study is the clinical efficacy of PPARa agonist fenofibrate add-on therapy in NFLE patients, which exhibited remarkable seizure reduction with good control of the disease.…”
Section: Discussionmentioning
confidence: 81%
“…CHRNA4 encodes a4 subunit of the neuronal nicotinic acetylcholine receptor (nAChR), frequently assembled with the b2 subunit (encoded by CHRNB2) into a heteropentamer a4b2-nAChR. The tertiary structure of each subunit is similar, comprising four transmembrance domains (M1-M4) with N and C ternmini on the extracellular side [7]. The a4b2-nAChR mutations were previously reported to be mainly located in the M2 and M3 regions [8].…”
Section: Discussionmentioning
confidence: 99%